Conselhos Gestores de Políticas Públicas: entre a ampliação dos direitos sociais e a legitimação das decisões governamentais - Costa, Ana Maria Almeida da (2004)
The discussion present in this dissertation aims to reflect about the Councils that elaborate public social policies from the point of view of an alternative for increasing the participation of the civil society. Therein we search to understand the limits and the possibilities presented by this space and to answer if this relation contributes to the effectiveness and the increase of civil rights. Consequently some questions have pervaded the analysis as for the perspective of their instrumentality and representation as well as their importance as an instrument of social control of the organized civil society, when it comes to the formulation, inspection and accomplishment of actions, besides the employment of the resources reserved for the public social policies. From the historical point of view we restored some of the prime processes of the social and political organization of the Brazilian society in reference to the 80 s and the 90 s. The point was to examine the main political bonds between this movement and the social participation of popular layers. Therefore is justified the concern with the capacities of the Councils to increase, in a more democratic way, the debate about the whole of shifts to which submit themselves the most different social layers, specially the most destitute, so that it may contribute to the gradual major interaction with the users of public social policies. Meanwhile the political dimension of the representation was also a theme for reflection, either because of the necessity of appraisal of its legitimacy and the lead impressed in the discussions, or because of the limits of the assigned representation.